2013
DOI: 10.1007/s10815-013-9990-4
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in patients with oligozoospermia and non-obstructive azoospermia

Abstract: Purpose To assess the frequency and types of chromosomal abnormalities in 204 Ukrainian patients with non-obstructive azoospermia and oligozoospermia and 87 men with normozoospermia. Methods Cytogenetic studies were performed on peripheral blood lymphocyte samples of 164 men with oligozoospermia, 40 men with non-obstructive azoospermia and 87 men with normozoospermia attending infertility clinic. Results Chromosomal abnormalities were detected in 17 % of patients with sperm disorders: in 35 % of men with azoos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 29 publications
1
24
0
1
Order By: Relevance
“…while Dada et al [2] reported higher frequency (22.2%) by including only azoospermic and severe oligozoospermic (sperm count less than 5 million/ml). The higher frequency of chromosomal abnormalities in our NOA than SOZ men (22.6% versus 3.7%, respectively) was in agreement with the results of other studies suggesting that the prevalence of chromosomal abnormalities increases as the sperm count decreases [18,20,21,23,25,32,35,37] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…while Dada et al [2] reported higher frequency (22.2%) by including only azoospermic and severe oligozoospermic (sperm count less than 5 million/ml). The higher frequency of chromosomal abnormalities in our NOA than SOZ men (22.6% versus 3.7%, respectively) was in agreement with the results of other studies suggesting that the prevalence of chromosomal abnormalities increases as the sperm count decreases [18,20,21,23,25,32,35,37] .…”
Section: Discussionsupporting
confidence: 93%
“…Several studies [4,20,28,31,33,38,39] reported similar result [4,20,28,31,33,38,39] . However, in other studies, the frequency of structural abnormalities was higher than numerical ones [18,32] . These differences might be due to ethnic differences, different patient selection criteria and methodological aspects.…”
Section: Discussionmentioning
confidence: 72%
“…Karyotype abnormalities were identified in 7.2% of infertile males in Turkey (Cavkaytar et al, 2012) and the total prevalence of chromosomal abnormalities was found to be 4.3% (5/115) in Isparta (South of Turkey) (Kosar et al, 2010). Pylyp et al (2013) reported chromosomal abnormalities in 17% of Ukrainian patients with sperm disorders and Fu et al (2012) reported 11.55% of infertile Chinese men to have chromosomal abnormalities. The rate of chromosomal anomaly in men living in Central China was furthermore reported to be 6.84% (Liu et al, 2013) and abnormal chromosomal karyotypes were identified in 8.84% of infertile northeastern Chinese men and in 7.61% of male partners in Sichuan Province, China (Quan et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
“…In our present study, chromosomal alterations in the NOA men were 14.3%, which was higher than published data of the average level (8.2%) and the Indian average level (10.8%) (Akbari, Behjati, Pourmand, Asbagh, & Kachoui, ; Rao et al., ), and were lower than that in some Western countries (14.5%–26.3%) (Akbari et al., ; Akin, Onay, Turker, & Ozkinay, ; Frouzandeh, Saeideh, & Sanaz, ; Kate, Pokale, Jadhav, & Gangane, ; Mohammed et al., ; Rao et al., ). Such variability among different series is likely to be related to a dissimilar composition of the studied populations, mostly to the severity of male factor (Pylyp, Spinenko, Verhoglyad, & Zukin, ). Based on these observations, we proposed that the chromosomal alterations are important factors in male infertility in the Chinese population who underwent testicular biopsies.…”
Section: Discussionmentioning
confidence: 99%